Improving polymeric organic semiconductors through liquid chromatography - Müller, Sebastian (My University, 2025)
Polymeric organic semiconductors (OSCs) are a promising substitute to scarce metals in electronic devices. However, batches are often highly disperse and with variations in their molecular weight (MW) distributions. Moreover, their stiff backbones cause overestimations when measuring their MW relative to typical standards. To overcome this challenge, this project aimed to investigate the use of preparative high-performance liquid chromatography (HPLC) to isolate fractions of polymeric OSCs with narrow dispersities and varying MWs. A method was developed using poly(3-hexylthiophene) (P3HT) and subsequently applied to polydioctylfluorene (PFO), with the intention of using the latter as an alternative calibration standard. After optimization, the method demonstrated high reproducibility for P3HT and successfully produced narrow-dispersity fractions for both polymers. Future work should explore the suitability of the obtained PFO fractions as calibration standards.
Keywords: HPLC; SEC; GPC; miconductive polymers; P3HT; PFO; dispersity; persistence length; NMR